Instructional Leadership Role Through Kurt Lewin's Model to Enhance Culture of Change in Teacher Capabilities - Yazid Al Basthomi; Asep Sunandar; Agus Timan (Jurnal Educative: Journal of Educational Studies, 2023)
The purpose of this research is to describe (1) the essence of instructional leadership in change management in educational institutions and (2) the change process in an elementary school during the unfreezing, movement, and refreezing stages to enhance the teaching capabilities of a teacher at SD Negeri Wonokerto 04. The research method used is qualitative, using a phenomenological approach with a case study design at SD Negeri Wonokerto 04, Malang Regency. The data were collected using three techniques: in-depth interviews, participant observation, and documentary study. The analysis technique used is single-case analysis. To ensure data validity, the researcher performed triangulation, member checking, prolonged observation, and reference material adequacy activities. The results of this study indicate that instructional leadership plays a role as a controller in the change process. The micro-educational institution's change process in enhancing the teaching capabilities of teachers follows Kurt Lewin's change model, which consists of three phases: a) the unfreezing process using symposiums and "Kultin" (Routine Spiritual Sessions); b) the movement process using a workshop and the formation of an assistant team consisting of fresh graduate teachers; and c) the refreezing process carried out through collaborative workshops with SD Negeri Wonokerto 01 and the initiation of meta-learning.Tujuan penelitian ini untuk mendiskripsikan tentang: (1) esensi instructional leadership dalam manajemen perubahan pada lembaga pendidikan; (2) proses perubahan sebuah SD saat proses unfreezing, movement dan refreezing dalam peningkatan kapabilitas mengajar seorang guru SDN Wonokerto 04. Metode penelitian yang digunakan yaitu kualitatif melalui pendekatan fenomenologi dengan rancangan studi kasus di Sekolah Dasar Negeri Wonokerto 04, Kabupaten Malang. Data yang dikumpulkan dengan menggunakan 3 teknik, yaitu: wawancara mendalam, observasi peran serta, dan studi dokumentasi. Teknik analisis yang digunakan yaitu analisis kasus tunggal. Untuk memperoleh keabsahaan data, peneliti melakukan kegiatan triangulasi, pengecekan anggota, ketekunan pengamatan, dan kecukupan bahan referensi. Hasil dalam penelitian ini adalah instructional leadership mengambil peran sebagai pengendali proses perubahan dan proses perubahan sebuah lembaga mikro pendidikan dalam peningkatan kapabilitas mengajar guru yang mengacu pada teori perubahan model Kurt Lewin yang terdiri dari tiga fase, yaitu a) proses unfreezing menggunakan simposium dan Kultin (Kultum Rutin); b) proses movement menggunakan sebuah workshop dan pembentukan tim pembantu dari guru fresh graduate; dan c) proses refreezing dilaksanakan dengan workshop kolaborasi bersama SD Negeri Wonokerto 01 dan inisiasi meta learning